Protein-Derived Acetaminophen-Cysteine Can Be Detected After Repeated Supratherapeutic Ingestion of Acetaminophen in the Absence of Hepatotoxicity - O’Malley, GF (J Med Toxicol, 2015)
Generation of protein-derived acetaminophen-cysteine (APAP-CYS) is reported after ingestion of large and therapeutic dosages of acetaminophen in healthy and in liver-damaged patients. The incidence of protein-derived APAP-CYS adducts in repeated supratherapeutic dosages of APAP is not known. Methods: for 12 months, a standardized and comprehensive questionnaire was used to interview every consecutive patient at a pain management clinic. Patients found to ingest more than 4 g of APAP per day for a minimum of 14 consecutive days at the time of the encounter were invited to have blood drawn for hepatic transaminases and APAP-CYS adduct levels. Twelve subjects out of 990 interviewees met inclusion criteria. Ten of the 12 had measurable protein-derived APAP-CYS, none had evidence of liver injury. Patients that ingest repeated supratherapeutic amounts of APAP over several weeks may generate APAP-CYS protein adducts in the absence of hepatic injury.